POST-MODERN REFUTATION OF FAITH AND RELIGION: EXPLORING FOUCAULT’S ARGUMENT - Dr. Zulfiqar Ali (Journal of Islamic Thought and Civilization, 2012)
In this paper, I have developed and explored the possible Foucauldian refutation of faith and religion implicitly running through his major and minor writings. Foucault strongly disagrees with Kant‘s exposition of ‗pure reason‘ and ‗critique‘ providing room to faith and religion. On the basis of Foucault‘s conception of human reason, which runs parallel to Kant‘s conception, I have argued that Foucault strongly rejects faith. The Foucauldian reason being purely historical and contingent does not permit belief in entities beyond history and culture. And from the standpoint of Foucault‘s critique following from his conception of reason, I have argued that religion turns up as a severe threat to critique. When critique aims to break apart the subject and identities it comes in direct and violent conflict with the fundamentals of religion. At the end, I have identified the problem in Foucault‘s argument for future research.